Understanding Local Perspectives on Climate Change and Its Impacts on Small-Scale Fishing Communities in Honda Bay, Palawan, Philippines - Jesusito Vicente; Niño Jess Mar Mecha; Jean Beth Jontila (Studia Ecologiae et Bioethicae)
Climate change's adverse impacts are already evident, particularly in coastal areas. However, local perception that is essential in formulating policies for mitigating its impacts remains limited. Thus, this study evaluated the level of perception of small fishing communities on climate change and its impacts on livelihood and the environment. The data were obtained using a face-to-face survey with the aid of a structured questionnaire. They were interpreted and analyzed using the  Likert point scale, descriptive statistics, and chi-square. A total of 308 male fisherfolks participated in the survey. Majority belong to age 51-60 years old (38%) and 61 years old and above (32%). Most of them (65%) finished elementary and generally (94%) rely on fishing for main source of living. As for income, 47%  earned an estimated monthly income of Php 2,501-5,000 and 28% got  Php 5,001-7,500. Most of the respondents are full-time fishers (89%) for more than 11 years (87%), and fishing within the municipal water (92%). Majority  (90%) have an idea about climate change as reflected by their very high score in Likert Perception (24.3±2.3%). The climate change impacts perceived by the respondents include: increasing sea surface temperature (87%); fish are sensitive to changing climate (87%); and fossil fuel consumption contributes to climate change (84%). They said they got the information from TV/ Radio (99%) and social media (10%). The age (p-value < 0.0032) and source of information (p-value < 0.0348)  are among the variables with significant  relationship to the perception of respondents on climate change impacts. In total, it appears that majority of fishers are aware of the impacts of climates. It is suggested that effective management actions, such as emergency preparedness schemes and livelihood diversification should be explored to address the specific needs of fishing communities that are vulnerable to the impacts of climate change. Furthermore, an ecosystem-based approach that focuses on socio-economic dynamics and climate-induced changes in assessments and management is essential for the sustainable use of fisheries resources amidst the changing climate.